Police and Crime Commissioners: Developing and sustaining a new model of police governance in England and Wales - Loveday, Barry (International journal of police science & management, 2018)
This article considers the progress of the new system of police governance in England and Wales. It assesses the responsibilities and powers of Police and Crime Commissioners (PCCs) and examines local initiatives undertaken by some PCCs that have proved to have national ramifications. It evaluates the accountability of PCCs between elections and highlights the limited powers of Police and Crime Panels. It considers the convention of police operational independence in light of two controversial police investigations, and the potential need for PCC oversight of future publicly high-profile investigations. It provides an initial assessment of an important and recent High Court ruling (R v Police and Crime Commissioner for South Yorkshire, 2017) which, by making the PCC responsible for all police operational activity, questions the tradition of constabulary operational independence. It is argued that enabling the PCC to bring a chief officer to account for all police operations might mean that potentially challenging and fruitless investigations can be avoided in the future.